Perancangan Unit Pengisian Pada Mesin Pengisian Botol Otomatis Berbasis PLC - Junaidi; Yulfira; I Arif (Cered Indonesia Institute, 2022)
Currently, many people create a Micro, Small and Medium Enterprise (UMKM) for their source of income, both in terms of businesses engaged in the culinary world, fashion (fashion), and so on. One of them is the mineral water business in packaging. In this business, of course, the business owner must make a tool in order to meet the demands of consumers in terms of time and good results in the shortest possible time. This is the basis for the author to design an automatic filling machine with an MSME scale that will help business owners of bottled Mineral Water by pressing lower prices and making its application simpler for ordinary people to use technology. In designing the filling unit in this automatic liquid filling machine, a simple filling system is used. Nozzle only serves to stop the liquid flowing, continue the flow of water using only gravity as pressure to drain the liquid. The filling system in this liquid filling uses PLC as the main driving unit. . In the ladder diagram there are also several types of commands that are most often used in programming such as the TON (Time On Delay) command whose function is to determine the time of each automation process. The next command is the CTU (Counter Up) command whose function is to set the number of bottles that will be read by the sensor. In this study, the average speed for filling is Automatic filling of 500ml bottles takes about 15.62 seconds, while in 250 ml bottles requires a charging time of 7.81 seconds. In the design also found delay caused by automatic system programming of 3 seconds when pneumatic down, and 1 second when pneumatic up. So that in 1 minute, filling a 500ml bottle with a filling time of 15.62 plus a delay of 4 seconds, then in 1 minute the filling machine can fill 12 500ml bottles.